Keabsahan Perkawinan Semarga Masyarakat Adat Batak Ditinjau Dengan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Monica Belinda Oksavina (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2023)
Marriage in Batak traditional society is a sacred tradition and its implementation must adhere to the rules established by the ancestors. In Batak customs, intermarriage within the same clan is considered as incest, which is prohibited by Law No. 1 of 1974 concerning marriage. The legal requirement for a valid marriage is that it must be conducted according to the laws of each respective religion and belief system. The research journal utilizes a Normative Juridical approach, and the study is of a Descriptive Analytical nature. The research findings indicate that firstly, intermarriage within the same clan in Batak traditional society is considered valid and not prohibited by marriage laws. This is because intermarriage within the same clan does not fall under the category of incest as prohibited by Article 8 of the marriage laws. Secondly, if intermarriage within the same clan is still conducted, the customary legal consequence in Batak society is that the marriage is considered invalid, and there are customary sanctions that will be imposed if the intermarriage persists. However, from a national legal perspective, there are no clearly defined sanctions in the marriage laws for intermarriage or incestuous relationships.